PERAN GURU AGAMA HINDU DALAM KEGIATAN KOKURIKULER UNTUK MENGEMBANGKAN EKSISTENSI MODERASI BERAGAMA DI SD SARASWATI 6 DENPASAR - I Dewa Gede Darma Permana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
An exclusive attitude is a challenge for the plural and multicultural country of Indonesia. Overcoming these challenges, Hindu Religion teachers at Saraswati 6 Elementary School in Denpasar (SD Saraswati 6 Denpasar) play an active role in co-curricular activities to develop a moderate attitude in the school environment. This research then comes to identify specifically about the role of Hindu Religion teachers in co-curricular activities to develop the existence of religious moderation at SD Saraswati 6 Denpasar. This research uses qualitative research with a descriptive naturalistic approach. Through the use of primary and secondary data sources, data collection methods that use observation techniques, interviews, and literature studies, the results of this study indicate that, the role of Hindu Religion teachers in co-curricular activities leads to the utilization of flag ceremony activities, religious ceremonies, and guidance and counseling activities to foster moderate attitudes. The results of this study aim to guide other teachers and schools in developing the existence of religious moderation in the world of education.